THE PRAGMATIC MEANING OF MODALITY IN SPANISH LEGISLATIVE TEXTS: FROM ORDER TO POSSIBILITY - Vlasenko, Mary (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2025)
This article examines the pragmatic significance of modality in Spanish legislative texts, spanning from obligation (deber) to possibility (poder). It explores directive modality (expressing commands and duties), permissive modality (indicating rights and opportunities), and conditional modality (regulating hypothetical scenarios via subjunctive forms), alongside their syntactic features and variations across document types (e.g., Constitution, codes, decrees). The study draws on examples from Constitución Española, Código Civil, highlighting how modality shapes the communicative effectiveness of legal norms. Directive modality, prevalent in codes, ensures clarity of obligations, while permissive modality in constitutional texts underscores rights. Conditional modality, often complex due to subjunctive use, adds flexibility but risks ambiguity. The analysis reveals interpretation challenges stemming from modal ambivalence (e.g., poder as right or possibility), impacting legal application, as evidenced by judicial cases. Building on the dissertation’s communicative-pragmatic framework, the study contributes to understanding modality’s role in Spanish legal discourse, offering insights for linguistics and law. Future research could explore modality in digital legal texts or cross-cultural contexts. _______________ References: • Danylenko, (2015). Mova prava: istorychnyi i sotsiolinhvistychnyi vymiry. Lviv: LNU im. Ivana Franka. • Kravchenko, (2022). Prahmatychna adaptatsiia v perekladi yurydychnykh tekstiv. Kyiv: Vydavnychyi dim "KM Akademiia". • Lytvyn, (2020). Korpusnyi analiz modalnosti v ofitsiinykh tekstakh. Lviv: Vydavnytstvo Lvivskoi politekhniky. • Alcaraz Varó, (2019). El español jurídico en el siglo XXI. Madrid: Iustel. • Bhatia, K. (2020). Analysing Genre: Language Use in Professional Settings. London: Routledge. • Butt, & Benjamin, C. (2020). A New Reference Grammar of Modern Spanish. London: Routledge. • Fernández, (2021). Modalidad y pragmática en el español actual. Barcelona: Ariel. • Gibbons, (2018). Language and the Law: Linguistic Perspectives. Cambridge: Cambridge University Press. • Gotti, (2020). Legal Discourse across Cultures and Systems. Berlin: De Gruyter. • Martínez, (2022). Arcaísmos y formalidad en el lenguaje jurídico español. Sevilla: Universidad de Sevilla. • Moréteau, (2019). Comparative Legal Linguistics. New York: Springer. • Palmer, R. (2016). Modality and the English Modals. London: Longman. • Sánchez, (2022). Géneros textuales en el ámbito jurídico español. Valencia: Tirant lo Blanch. • Tiersma, (2017). Legal Language and Interpretation. Chicago: University of Chicago Press. • (1978). Constitución española. Madrid: Ed. Nacional. • (1988). Código Civil de España. Madrid: JACARYAN, S.A.